Finding the Poem - Modern Gaelic Verse and the Contact Zone - Corinna Krause (Forum, 2005)
Rather than "celebrating the joyous carnival of cultural differences", contemporary translation and publication practices dominating the contact zone which is Gaelic verse might well be evidence of bilingualism's "uglier face" resulting in "some kind of double monolingualism." (Grutman 224) This article will argue towards the re-evaluation of translation in this particular contact zone as a site of friction and differences between languages and cultures which is in need of translation and publication practices which resist the illusion of one-to-one equivalence.